1986
DOI: 10.2466/pr0.1986.59.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Employee Withdrawal: Effects of Locus of Control on Turnover

Abstract: Tested were two hypotheses concerning the role of locus of control in the process of employees' turnover: first, that employees with external locus of control would be more likely to intend to quit and actually quit their jobs, and second, that external scorers would be more likely to intend to quit and actually quit a dissatisfying job. Analyses supported only the aspect of intention to quit in both hypotheses. Externality was associated with intentions to quit, and locus of control moderated the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Researchers have also considered the influence of locus of control on withdrawal behnviour in work settings. Spector & Michaels (1986) found externality to be associated with intentions to quit, although this relationship did not hold for actual turnover. Rahtnan & Kumar (1984) found absenteeism to be independent of locus of control.…”
mentioning
confidence: 71%
“…Researchers have also considered the influence of locus of control on withdrawal behnviour in work settings. Spector & Michaels (1986) found externality to be associated with intentions to quit, although this relationship did not hold for actual turnover. Rahtnan & Kumar (1984) found absenteeism to be independent of locus of control.…”
mentioning
confidence: 71%
“…The third possible response to frustration is withdrawal from the situation (e.g., disengagement [Rothmann & Hamukang'andu, 2013], intention to quit [Spector & Michaels, 1986], and turnover [Marrow, 1972;O'Connor et al, 1984]). Withdrawal usually happens under conditions of high frustration, especially when other courses of action are inhibited and aggression is punished (Lazar et al, 2006;Spector, 1978;Storms & Spector, 1987).…”
Section: Founder Power and Full Venture Exit Via Ipomentioning
confidence: 99%
“…It was also assumed that all participants were employed in teaching positions in their respective workplaces (rather than other types of position). While retention and satisfaction both represent long term outcomes of a successful placement, several studies have found them to be uncorrelated ( Spector and Michaels, 1986 ; Boswell, 2006 ; Furnham, 2009 ; Lizano and Mor Barak, 2015 ; Boswell et al, 2017 ). Thus they may potentially represent distinct markers of a successful placement in some contexts.…”
Section: Literature Reviewmentioning
confidence: 99%